KAJIAN PENGGUNAAN KOTAK PENDINGIN MENGGUNAKAN HANCURAN ES UNTUK DISTRIBUSI PAK CHOI (Brassica rapa) - Emi Y. Sagas; Frans Wenur; Lady C. Ch. E. Lengkey (Universitas Sam Ratulangi, 2015)
Abstract This study aims to Calculating the amount of ice needed to cool the water to 150C in a pre cooling and explain changes in visual quality and extent of the damage vegetable pak choi on cooling than without cooling for 5 days. With this research is expected pak choi farmers and traders can use simple cooling technology. In addition to the application of cooling technology is expected to extend the shelf life pak choi, which in turn will increase profits for farmers and traders pak choi. The results showed that the amount of ice needed to lower the water temperature from 250C becomes 150C is 4.83 kg of ice. In the cold storage for 5 days does not change the quality of pak choi, leaf color still looks fresh with a percentage of 100% quality. While pak choi without refrigeration on the last day of storage and the percentage of damage pak choi untreated cooling on the fifth day of storage at 100%.